INTEGRATING PRINT AND DIGITAL MEDIA FOR TARGETED MARKETING IN URBAN AND RURAL AREAS - Garg, Ankit Kumar; Singh, Chandan; Soni, Kartik; Agrawal, Pranjal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The evolving landscape of marketing presents significant opportunities and challenges for businesses aiming to reach both urban and rural audiences. While digital marketing has gained prominence with the rise of internet penetration and mobile usage, print media continues to hold relevance, especially in rural regions. This paper explores the integration of print and digital media to design effective, targeted marketing strategies that cater to the unique needs and behaviours of consumers in urban and rural areas. Through a mixed-methods approach, this study examines how these two forms of media can complement each other, ensuring broad reach and engagement while addressing local preferences. Findings suggest that combining the immediacy and personalization of digital marketing with the trust and familiarity of print media enhances consumer awareness and brand loyalty. This integration can be especially beneficial in rural areas where digital access may be limited but print still holds considerable sway. By leveraging the strengths of both mediums, businesses can create tailored marketing campaigns that resonate with diverse demographic groups, driving better consumer outcomes across varied geographic regions.